Harnessing nature-based solutions for health in post-COVID era: a narrative review - Aikat, Aditi; Roy, Megha (International Journal Of Community Medicine And Public Health, 2024)
In the post-COVID era, nature-based solutions (NBS) has emerged as a promising paradigm to address the health challenges at the human-animal-environment interface. This narrative review explores the dynamics between NBS and human health and the diverse mechanisms involved, substantiated through different domains of evidence like biomechanistic studies, exposure science, epidemiology, and implementation science-based research. Ranging from forest management, urban green spaces to control health hazards from air pollution to blue infrastructure safeguarding against waterborne diseases, NBS interventions has the potential to favor public health outcomes positively. Besides, psychological benefits of NBS, in reducing stress, and improving mental well-being has been pivotal in addressing the mental health crisis. Although differential access to green and blue spaces is a vexing issue that needs equitable distribution of NBS interventions to maximize health equity. Harnessing the inherent capacity of natural ecosystems, NBS provides tangible health benefits while fostering sustainable, healthy living.